Stand and deliver : how to become a masterful communicator and public speaker (Simon & Schuster, 2011)
Stand and Deliver gives you everything you need to know to become a poised, polished, and masterful communicator. It reveals the techniques that have worked for countless great speakers throughout history. In this book you will learn how to prepare properly for a presentation, develop and project your own unique style, overcome stage fright, and win any audience in one minute. Packed with tips, strategies, and real-life examples, including case studies of some of the world's great orators, Stand and Deliver is the definitive guidebook for public speaking.